The Procedure For The Formation Of Strictly Agreed Prices In Construction - Amirov Zubaydullo Toirovich; Bozorov Bobur Khakberdievich (Genius Journals, 2022)
Without the rules and regulations of pricing and coordination, it will be difficult to establish optimal prices. In connection with the transition to free-market prices in a market economy in the construction industry, a number of difficulties arise in the formation of prices in comparison with other sectors of the economy.
Keywords: investment; capital investment; construction; price